Exploring Teachers’ Perceptions and Practices on Teaching Learning Strategies and Learning Materials Used in ECE Classrooms in Gilgit - Ferkhanda Jabeen, Dil Angaiz (JECCE, 2023)
Teachers' perceptions have been shown to influence their teaching practices (Ashiabi, 2007; Erwin & Delair, 2004). Hence, it is imperative to explore how ECE teachers' perceptions affect the way they teach and perceive their students’ learning skills (Yeung, Craven, & Kaur, 2014). This qualitative case study is intended to explore Teachers’ Perceptions and Practices on Teaching-Learning Strategies and Learning Materials used in ECE classrooms in Gilgit. Ten early childhood education teachers of private schools were selected through purposive sampling. Data was collected through semi-structured interviews, observations and document analysis. Findings of the study revealed inconsistencies between ECE teachers’ perceptions and practices. ECE teachers claimed that they implement play way as teaching learning strategy and use learning materials as children actively involved in play. However, mainly teacher directed approach was observed to practice by the participant teachers in their classrooms. Analysis revealed that these discrepancies are due to; lack of practical skills to implement theoretical knowledge, inadequate learning materials, time and space limitations, and pressure from key stake holders. It is therefore recommended that ECE teachers be trained and supported by providing opportunities to improvise their teaching strategies so that they can implement ECE policy with its full essence.